PENATAAN SISTEM, PROSEDUR, DAN ORGANISASI GALERI UMKM KECAMATAN PONCOKUSUMO KABUPATEN MALANG - Pudji Herijanto; Nilawati Fiernaningsih; Widjanarko Wijanarko; Fauzi Ahmad; Maskur Maskur; Suwarni Evi (Dharma: Jurnal Pengabdian Masyarakat, 2022)
The purpose of opening the gallery is to add distribution channels for MSME products, in order to increase sales. Most of these MSMEs produce products with local raw materials so they play a role in increasing the added value of the area. Currently, gallery operations are handled by the UMKM Association while still implementing traditional store management. After running for more than a year, they are still unable to carry out their functions effectively. This Community Service Activity aims to organize the Gallery's Organizational, System, and Working Procedures. The m Evi Suwarni method of implementing the activities is done by transferring knowledge, simulation, and implementing the gallery's organization, system, and work procedures. Evaluation of participants' understanding was done by distributing questionnaires. The output of this service is an increase in the knowledge and skills of partners, especially in terms of gallery management and the completeness of gallery operational standards. Another outcome is an increase in the competitiveness of partner human resources, who have knowledge and skills in managing galleries, both in terms of organization and work procedures. Store services also become another competitive advantage in the production process, especially consignment sales services.Keywords: system, procedures, organisation, gallery